Skin grafting in the treatment of open injuries of hand and fingers - Goridova, Lidia; Shevchenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The amount of open injuries of hand and fingers is equal to 55.1 % among all hand injuries and their consequences. They are often associated with tissue defect and lead to the loss of hand function. These injuries are recommended for surgical treatment with skin grafting in order to avoid amputation of injured segment. Different variants of autografting are summarized and illustrated in the article. The choice of autografting method depends upon the features of damage and clinical task — free (epidermis flaps, split-thickness and full-thickness skin grafts) and non-free (Italian, Filatov-Gillies pedicle grafting) flap coverage of wound. Their advantages and disadvantages are listed. The requirements for the performing of different types of grafting are identified. The peculiarities of prevention of cicatrical contraction development are described. Author draws attention to the special features of palm skin on hand and fingers, that limits usage of local skin flap. Methods of wound coverage on fingers and hand depend on their localization, size, and depth of tissue damage. Recommendations for coverage of donor wounds are noted. The necessity of saving of the finger terminal phalanges, especially 1st finger, is emphasized. Author showed the treatment techniques in the cases of butt defects of fingers.